Pronunciation learning attitudes: The case of EFL undergraduate students in Indonesia - Toni Indrayadi; Herri Mulyono; Sri Kusuma Ningsih; Amirul Mukminin (Universitas Syiah Kuala, 2024)
A pronunciation-learning attitude is essential to help students improve their pronunciation proficiency. It is problematic when students do not care about learning proper pronunciation in the process of teaching and learning. Several studies have investigated EFL students perceptions toward attitudes of pronunciation learning. However, little research focused on the role of gender on students attitudes in this context. Therefore, the present study aimed to investigate students attitudes toward English pronunciation learning related to gender. An explanatory sequential mixed-method approach, integrating questionnaires of Gardner 1985s Attitude Motivation of Test Battery (AMTB) and Elliot 1995s Pronunciation Attitude Inventory (PAI) and interviews, was employed in this study. Descriptive and inferential statistical analyses were used to analyse quantitative data gathered from 151 students. For qualitative data, the semi-structured interview transcripts of eighteen participants were analysed using thematic analysis. The questionnaires reveal that the students had positive pronunciation learning attitudes, and no significant differences were found between females and males. Moreover, based on the results of the interviews, the students believed that proper pronunciation learning is important to make the message understood. Reflecting on the study results, it is hoped that English lecturers select more practical pronunciation teaching media that can make students more involved in the teaching and learning process and contribute to English pedagogy about the importance of improving learners positive attitude in pronunciation learning.